Experimental investigation of negative index materials - Ong, Ran Xing. (2009)
Metamaterials are materials that are structurally engineered to exhibit properties that do not exist in nature. An example of metamaterial is the negative index material. One of the applications of negative index material is in the area of cloaking. There are many shapes and patterns that have been theorized and shown to exhibit negative index. One of them is the multi-layered structure of alternating layers of ferrite and another material, such as metal, dielectric or superconductor.